2014
DOI: 10.1088/1674-1056/23/3/036102
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution of zircaloy-4 during Ne ion irradiation and annealing: Anin situTEM investigation

Abstract: The microstructural evolution of zircaloy-4 was studied, including the amorphization and recrystallization of Zr(Fe, Cr) 2 precipitates, and the density of dislocations under in situ Ne ion irradiation and post annealing. The results show that irradiation at a relatively high temperature and dose induces the formation of nanocrystals in pre-amorphized Zr(Fe, Cr) 2 precipitates. The recrystallized nanocrystals also have the structure of hcp-Zr(Fe, Cr) 2 . The formation of the nanocrystals is thought to be the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The ion implantation energy was set at 400 keV with the sample normal direction, which would result in a projected range of 1330 nm that was calculated by SRIM code. [33,34] The SRIM code was also used to simulate the He irradiation induced damage and He concentrations in the Ti 3 SiC 2 matrix and the used displacement energies were 25 eV, 25 eV, and 28 eV for Ti, Si, and C, [12,35] respectively. The helium fluence was in a range from 0.5 × 10 17 He + /cm 2 to 2.0 × 10 17 He + /cm 2 , and the helium flux was set at 0.78 × 10 14 He + /(cm 2 •s) to avoid the severe irradiation heating.…”
Section: Helium Irradiationmentioning
confidence: 99%
“…The ion implantation energy was set at 400 keV with the sample normal direction, which would result in a projected range of 1330 nm that was calculated by SRIM code. [33,34] The SRIM code was also used to simulate the He irradiation induced damage and He concentrations in the Ti 3 SiC 2 matrix and the used displacement energies were 25 eV, 25 eV, and 28 eV for Ti, Si, and C, [12,35] respectively. The helium fluence was in a range from 0.5 × 10 17 He + /cm 2 to 2.0 × 10 17 He + /cm 2 , and the helium flux was set at 0.78 × 10 14 He + /(cm 2 •s) to avoid the severe irradiation heating.…”
Section: Helium Irradiationmentioning
confidence: 99%
“…Titanium film has the advantages of good hydrogen absorption performance, high thermal stability, and low room temperature equilibrium pressure. Ti film has been used as a metal hydride in the solid phase and has played an important role in the fields of hydrogen storage [35], solar thermal energy storage [36], and nuclear energy storage [4,37,38,39]. It has been reported that the surface morphology and grain size of Ti film on a Mo substrate was severely affected by the heterogeneity of polycrystalline Mo [4,38,40].…”
Section: Introductionmentioning
confidence: 99%
“…Defects and damage induced by energetic heavy ion irradiation in materials have been an interesting research subject. [5][6][7][8][9] Mica is one of the earliest materials to be used to investigate the irradiation effects of swift heavy ions (SHIs) and highly charged ions (HCIs). Etching tracks on mica induced by charged particles were observed first by Price in the 1960s.…”
Section: Introductionmentioning
confidence: 99%